The Concept of Corporate Social Responsibility in Institutional Economics - Lulewicz-Sas, Agata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The concept of corporate social responsibility is not well established in economics. It has been analysed in equal measure from two perspectives - economics and management science. The theoretical foundations of the concept of CSR can be traced to the concept of institutional economics, particularly transaction cost theory. This article attempts to locate the concept of corporate social responsibility in the framework of institutional economics.